(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25^2 -1)(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25-(a.b^2-a) với a= -1 , b=(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25 25(a^2 +b^2 -1)-(a.b^2(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25-a) với a= -1 (a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25(a^2 +b^2 -1)-(a.b^2-a) với a= -1 , b= 25=5 25
\(A=1+2+2^2+...+2^{100}\)
\(\Rightarrow\)\(2A=2+2^2+2^3+...+2^{100}+2^{101}\)
\(\Rightarrow\)\(2A-A=\left(2+2^2+2^3+...+2^{100}+2^{101}\right)-1+2+...+2^{100}\)
\(\Rightarrow\)\(A=2^{101}-1\)